Isolation of dioscin-related steroidal saponin from the bulbs of Allium paradoxum L. with leishmanicidal activity - Fatemeh Rezaee; Behzad Zolfaghari; Masoud Sadeghi Dinani (Wolters Kluwer Medknow Publications, 2018)
Alliums are rich sources of steroidal saponins, flavonoids, and sulphoric compounds of which steroidal saponins have recently received more attention due to their important pharmacological activities. Allium paradoxum L. is a common edible vegetable in north regions of Iran, especially in Mazandaran province, where it is named "Alezi" and considerably used as a raw vegetable, to make dishes, and as a medicinal plant. Phytochemical investigation of chloroform-methanol extract of the plant resulted in the isolation and identification of a dioscin related steroidal saponin, using comprehensive spectroscopic methods including 1D and 2D NMR, its chemical structure was determined as (25R)-spirost-5-en-3b-ol,3-O-α-rhamnopyranosyl-(1→4)-α-rhamnopyranosyl-(1→4)-[a-rhamnopyranosyl-(1→2)]-glucopyranoside. Investigation of in vitro antileishmanial activity of the isolated compound, in 10 and 50 μg/mL concentrations, exhibited significant leishmanicidal effects (P < 0.001) against the promastigotes of Leishmania major. The results established a valuable basis for further studies about A. paradoxum and anti-parasitic activity of steroidal saponins.